Persepsi Guru PAI dan Praktek Penilaian Sikap Pada Kurikulum 2006 dan K Kurikulum 2013 S tudi Kasus di SMSMP Negeri Kecamatan Turi dan Sleman - Endah Sri Winarni (Kopertais Wilayah III Yogyakarta, 2018)
The background of this research is the problem of people>s concern about juvenile delinquency. Nowadays, the government plan and practicing 2013 curriculum. With the application of 2013 curriculum, the education would be expected to be focused on character development for student, so that the problem of juvenile delinquency can be solved. This study is aimed at finding out some impacts. First, to know the perception of Islamic Education Teacher about the character assessment that conducted in 2006 curriculum in Junior High School, particularly in Turi and Sleman sub-district. Second, to know the perception of Islamic Education Teacher about the character assessment that conducted in 2013 curriculum in Junior High School, particularly in Turi and Sleman sub-district. Third, to know the implementation of character assessment that is conducted on 2006 curriculum, particularly in Turi and Sleman sub-district. Fourth, to know the implementation of character assessment that is conducted on 2013 curriculum, particularly in Turi and Sleman sub-district. The data of this research were analyzed using descriptive or qualitative techniques. This research conducted at Junior High School, especially in Turi and Sleman sub-district. The data were collected by doing interview, observation, and documentation. The finding reveal four important results. First, character assessment which is conducted on 2006 curriculum is followed by all teachers, each teacher has to assess their students not only several teacher. Second, the practice of character assessment that is conducted on 2006 curriculum is using observation technique. There were some techniques applied: observation, istiqomah paper, and case study report. Third, the character assessment on 2013 curriculum is more systematic and objective because the technique that is used on 2013 curriculum is more emphasized on actual event which is happened inside or outside class. Fourth, the practice of character assessment on 2013 curriculum use some technique, there are observation, journal, self-reflection and collaborative assessment.